First records of two orthocentrine genera (Hymenoptera: Ichneumonidae) from India with description of two new species - Ranjith, A.p.; Humala, Andrei E.; Priyadarsanan, Dharma Rajan (Zootaxa, 2022)
The orthocentrine ichneumonid genera Gnathochorisis and Symplecis are reported for the first time from India with the description of two new species. Taxonomic keys for the identification of Indomalayan Gnathochorisis and Symplecis are provided along with the illustration of the new species.